EU-Russia strategic relations: A gas issue - Bozayeva, Zhanyl (My University, 2015)
This thesis considers the European Union-Russia gas relations in the context of three different time periods: the Cold War, post-Cold War and post-2014 Ukrainian crisis. The aim of the thesis is to understand and evaluate the EU-Russia energy relations, identify the basic principles of these relations and examine the changes that occurred after the end of the Cold War. The findings of the thesis have shown that the energy dialogue between Brussels and Moscow has been changing and has illustrated different characteristics in different periods of time. Despite these changes, the thesis concludes that the energy dialogue between the parties since its inception to the most recent period has been based on mutual interdependence. The 1st period covered the years from 1913 to 1991. The Cold War gas/energy relations between the parties, despite the hostile atmosphere of the Cold War period, were based on a commercial partnership, that is, the parties were believed to interact with each other mostly because of business considerations. During the Cold War gas relations period the Soviet Union constructed an image of a reliable gas supplier. Within the next period (1991-2014) this commercial partnership was substituted by the strategic partnership; however, the Russian image as the dependable supplier was tarnished. Despite this fact, the European policy towards Russia was based on the “Russia First” approach, so the interests of the so-called “New Europe” (Central and Eastern Europe) within the energy dialogue were disregarded. However in the wake of the 2014 Ukrainian crisis the “Russia First” approach started to be questioned by Brussels. Such kind of change could herald the beginning of the 3rd phase in the EU-Russia energy dialogue, as Brussels attempts to replace the existing “Russia First” approach by a new “Eastern Europe First” approach.

Bu yüksek lisans tezi Soğuk Savaş, Soğuk Savaş sonrası ve 2014 Ukrayna krizi sonrası dönemlerindeki Avrupa Birliği-Rusya gaz ilişkilerini değerlendirmektedir. Bu tezin amacı Rusya ve Avrupa arasındaki stratejik gaz/enerji ilişkilerini tarihsel süreci değerlendirerek kavramak, gaz/enerji ilişkilerinin temel dayanaklarını tespit etmek ve Soğuk Savaş sonrasındaki değişimini incelemektir. Bu çalışmanın bulguları Brüksel ve Moskova arasındaki enerji diyaloglarının farklı dönemlerde farklı özellikler taşıdıklarını göstermektedir. Enerji diyaloğundaki yaklaşımların değişimlerine rağmen taraflar arasındaki bu diyalog başlangıcından bu yana karşılıklı bağımlılık temeline dayanmıştır. Araştırmanın 1. Dönemi 1913-1991 yıllarını kapsamaktadır. Bu dönemin sonucunda taraflar arasındaki gaz ilişkilerinin Soğuk Savaş dönemindeki düşmanca atmosfere rağmen ticari ortaklığa dayalı olduğu kanısına varılmıştır. Başka bir deyişle, taraflar birbirleriyle çoğunlukla ticaret nedeniyle etkileştiği sonucu çıkarılmıştır. 1. Dönem süresince Sovyetler Birliği’nin (Rusya’nın) güvenilir bir gaz tedarikçisi imajını inşa ettiği görülmüştür. Sonraki dönemde — 1991-2014 yılları arasında — taraflar arasındaki mevcut ticari ortaklığın stratejik ortaklık olarak değişime uğradığı gözlemlenmektedir; bununla birlikte Rusya’nın güvenilir gaz satıcı imajının zedelendiği belirlenmiştir. Buna rağmen bu dönemde Avrupa’nın Rusya’ya karşı politikasının “Öncelikli Rusya” yaklaşımına dayandığı tespit edilmiş ve bu yaklaşımın sonucunda sözde “Yeni Avrupa” (Orta ve Doğu Avrupa) ülkelerinin çıkarları göz ardı edilmiştir. Ancak 2014 Ukrayna krizinin ortaya çıkmasıyla birlikte Brüksel bu “Öncelikli Rusya” yaklaşımını sorgulamaya başlamıştı. Böyle bir sorgulama 3. Dönemin başlamasının habercisi olabilir. Ve bu durumda AB Rusya’ya olan “Öncelikli Rusya” yaklaşımını “Öncelikli Doğu Avrupa” yaklaşımıyla değiştirmeye çalışabilir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2015
Keywords: Russia; European Union; Natural gas; Gas disputes; EU-Russia energy; Dialogue; Energy interdependence